In vitro propagation and andrographolide analysis of Hempedu Bumi (Andrographis paniculata Nees). - Paritala Vikram (2016)
Andrographis paniculata and andrographolide have huge potential in medical industries resulting in higher market demand of the plant. To meet the requirement of A. paniculata, micropropogation by organogenesis, embryogenesis and secondary metabolte production by callogenesis were studied in the present study. In order to develop an efficient protocol for propagation, organogenesis studies were carried out using leaf, shoot tip, embryonic explants and transverse thin cell layers (tTCL) cultured in Murashige and Skoog media supplemented with various cytokinins either alone or in combination of auxins. The highest number of multiple shoots were regenerated from nodal tTCL explants (16 shoots/explant) followed by embryo explants (12 shoots/decapitated embryonic axes and 9 shoots/cotyledon), shoot tips (6 shoots/explant) and leaves (6 shoots/explant). Among the plant growth regulators tested, thiadiazuron was found to be the most effective hormone in producing multiple shoots in most of the explants followed by benzyl aminopurine and kinetin while 2-isopentenyl adenine was found to be least effective to induce organogenic response. The shoots were successfully elongated in kinetin 1.0 mg/L/ indolebutyric acid 0.5 mg/L and rooted in vitro in half strength MS media containing indolebutyric acid 0.5 mg/L alone with an average root number of 7.4 and root length of 4.0 cm. Acclimatization of rooted plantlets was successfully carried out with 78% survival rate using polybags. Somatic embryogenesis was induced using zygotic embryo explants in media containing different auxins alone or in combination of cytokinins and the highest embryogenesis percentage (75%) and average number of embryos (23 embryos/explant) were observed in media with napthaleneacetic acid 1.5 mg/L/ kinetin 1.5 mg/L. The somatic embryos were converted into synthetic seeds by encapsulating with 3.0% sodium alginate; however the germination rate of somatic embryos was reduced from 60% to 30% upon encapsulation. Callus cultures were established from zygotic embryo explants on different auxins alone or in combination of cytokinins. Different auxins showed different kind of callusing or rooting response based on the concentration and combinations with cytokinins. Napthaleneoxyacetic acid 1.5 mg/L/ benzylaminopurine 0.75 mg/L showed highest amount of callus while napthaleneacetic acid recorded highest amount of adventitious roots. Analysis of andrographolide content in the callus and root cultures showed the presence of andrographolide highest in rhizogenic callus of napthaleneacetic acid 3.0 mg/L (2.4 mg/gm of dry weight) making embryo culture feasible and realistic for andrographolide production in vitro. Callus produced on media with napthaleneoxyacetic acid 1.5 mg/L+ benzylaminopurine 0.75 mg/L had more antioxidant capacity with inhibitory concentration (IC50) value of 20.91 μL and total phenolic content of 0.88 gallic acid equivalent mg/g compared to roots produced on napthaleneacetic acid 3.0 mg/L. In vitro organogenesis in A. paniculata using tTCL and embryo explants is reported for the first time in this study and this method can be used as an efficient protocol for clonal propagation of A. paniculata.